Effect of Componential Proportion in Bimetallic Electrocatalysts on the Aprotic Lithium‐Oxygen Battery Performance. Issue 20 (14th April 2018) - Luo, Xiangyi; Ge, Le; Ma, Lu; Kropf, Arthur J.; Wen, Jianguo; Zuo, Xiaobing; Ren, Yang; Wu, Tianpin; Lu, Jun; Amine, Khalil
Abstract: Rechargeable lithium‐oxygen (Li‐O2 ) batteries are one of the most promising technologies for next‐generation energy storage, which is also a critical part of the future renewable energy portfolio; however, its commercialization is still hindered by several challenges. The high charge overpotential, in particular, not only causes problems by increasing the possibility of electrolyte decomposition but also induces a low round‐trip efficiency and coulombic efficiency. Here, by choosing the right component proportion in Pt‐Cu bimetallic electrocatalysts that optimize electrocatalytic activity of electrochemical reactions, especially of oxygen evolution reactions, a superior electrochemical behavior is demonstrated, with a low charge overpotential of 0.2 V and cycleability of 50 discharge/charge cycles before capacity fading. The optimized Pt‐Cu bimetallic electrocatalysts significantly reduce the charge overpotential and furthermore enhance the efficiency, stability, and cycleability of an aprotic Li‐O2 battery. Abstract : The reported Pt‐Cu bimetallic materials are composed of mostly CuPt intermetallic phases (CuPt, CuPt7 ) and partially covered by CuO. By choosing appropriate component proportions, the material's electrocatalytic activity is optimized. This is demonstrated through an oxygen evolution reaction in an aprotic lithium‐oxygen battery.